PRINCIPLES OF DESIGNING MODERN SPORTS COMPLEXES - Anvarjonova Mohichehra Rasuljon qizi (Research Focus International Scientific Journal, 2025)
Modern sports complexes play a key role in the development of sports culture and the promotion of a healthy lifestyle in society. The creation of such complexes requires a comprehensive approach that takes into account the diverse needs of users, innovative technologies, and principles of sustainable development. This article examines the main principles of designing modern sports complexes based on the analysis of current trends and best practices.